LEGAL BASIS FOR FIGHTING CORRUPTION - Nodirbekov Furqatbek Umarjonogli (International Journal of Innovations in Engineering Research and Technology, 2021)
Corruption and its causes, the role of Uzbekistan in the ranking of International Anti-Corruption Organizations, measures to prevent corruption and the laws adopted, the mechanism of their implementation are described in detail.